Functional complementation of mitochondrial DNAs: Mobilizing mitochondrial genetics against dysfunction - Schon, Eric A.; Gilkerson, Robert W. (Biochimica et biophysica acta, 2010)
Human mitochondrial DNA (mtDNA) is a 16.6-kb circular genome that is typically found in ∼ 1000 copies per cell. Frequently, one or more forms of mtDNA (i.e. wildtype (WT) and one or more mutant variants) will co-exist within an individual cell, a situation termed heteroplasmy; however, it has been unclear how different mitochondria and mtDNA populations interact functionally in a heteroplasmic cell system. Using sequence-specific microscopic methods to examine mtDNA at suborganellar resolution, we examined the submitochondrial organization of mtDNA heteroplasmy in nucleoids, the DNA–protein complexes that organize and package mtDNA. Our recent results reveal that, while heterologous mtDNAs are generally maintained stably in separate nucleoid populations, the two mtDNAs transcomplement each other to restore WT-like levels of mitochondrial function and morphology. These findings reveal that the diffusion of mtDNA-derived transcripts through the mitochondrial matrix allows for transcomplementation, despite the apparent genetic autonomy of nucleoids. The fundamental ability of mtDNAs to complement each other within the matrix of the mitochondrial network provides a mechanistic basis for therapeutic strategies designed to restore mitochondrial function in heteroplasmic cells by increasing WT mtDNA content, particularly in light of the emerging connection between the processes of mitochondrial fission/fusion and mtDNA nucleoid organization.